Implementation Indonesian Government Policy On Sales In Tiktok Shop Application - Wiganda, Aldi Pangestu; Azhar; Alamsyah (Jurnal Disrupsi Bisnis, 2025)
This research aims to analyze the implementation of the Indonesian government's policy on sales at TikTok Shop, especially to reveal its overall impact. The research method used is qualitative, combining literature review and policy analysis. The results show that there is a complexity of regulations trying to balance consumer protection, business growth, and tax compliance. While efforts have been made to improve transparency and fairness in online commerce, challenges in law enforcement, adaptation to market changes, and inclusive growth of the digital economy remain key concerns. The implications of this research point to the importance of adaptive and progressive regulation to create a conducive environment for innovation and sustainable growth of the digital economy in Indonesia, as well as ensuring strong protection for consumers and fairness in business competition. As such, this research offers valuable insights for policy makers, business players, and the general public on the complexity and urgency of regulation in governing e-commerce in this digital era.